Infrared thermography as an injury prevention method in soccer - Gomez, P. M.; Sillero, M.; Noya, J.; Pastrano, R. (Archivos de medicina del deporte, 2008)
Infrared thermography is considered as a valid and non-invasive diagnostic method of different pathologies, including some musculo-skeletal problems as the lumbar pain. Modern equipments make possible very accurate and objective recording of the body surface with a single picture. Materials and methods: We recorded the body temperature of 23 professional players of the C.D. Toledo S.A.D. (Age= 24,9; SD= ± 3,5) on 24 days of its 2-months precompetitive period. Two thermographic pictures for each player (frontal and dorsal, of the trunk and lower limbs) were taken with a ThermaCAM TM SC640 (FLIR SYSTEMS, Portland) before starting the training season. Mean temperature of the muscular groups: abdominal (AB), quadriceps (QR,L), adductors (ABR,L), anterior leg (ALR,L), lumbar (L), hamstrings (HR,L) and calves (CR,L) and the joints: anterior knees (AKR,L), posterior knees (PKR,L), ankles (AR,L) were calculated from the pictures by the software "ThermaCAM Reporter". Additionally, the level of nuisance of those areas was assessed every day by the player from 1 (no pain) to 10 (injured). Temperatures were compared with the declared level of nuisance considering three groups (1 = No pain; 2 - 3 = Low pain; > 4 = High pain). Areas affected by physiotherapeutic treatments were excluded from the sample. Rough reports and pictures from each player were daily reported to the physiotherapist of the team. Results: ANOVA results point out a direct relationship between the declared level of nuisance of the area and its temperature both in ankles (F[AR] = 9.20; p < 0.05 and F[AL] = 3.99; p < 0.05) and knees (F[PKR] = 5.34; p < 0.05 and F[PKL] = 9.14; p < 0.05). There were also found signifi cant differences for temperatures (˜ 0.5 degrees) between the painful and non-painful limb on the knee (F[AK] = 14.36; p < 0.05) and hamstring (F[H] = 3.09; p < 0.05) results. None serious injury has been produced among the players during the 2-months of the study. Conclusion: We concluded that infrared thermography is a valid, fast and convenient method of preventing soccer injuries. We suggest that this technique could also be applied to monitor and diagnose injuries and to quantify training loads in sports.